The regulon of the RNA chaperone CspA and its auto-regulation in Staphylococcus aureus - Caballero, Carlos J; Menendez-Gil, Pilar; Catalan-Moreno, Arancha; Vergara-Irigaray, Marta; García, Begoña; Segura, Víctor; Irurzun, Naiara; Villanueva, Maite; Ruiz de los Mozos, Igor; Solano, Cristina; Lasa, Iñigo; Toledo-Arana, Alejandro (Nucleic acids research, 2018)
Abstract RNA-binding proteins (RBPs) are essential to fine-tune gene expression. RBPs containing the cold-shock domain are RNA chaperones that have been extensively studied. However, the RNA targets and specific functions for many of them remain elusive. Here, combining comparative proteomics and RBP-immunoprecipitation-microarray profiling, we have determined the regulon of the RNA chaperone CspA of Staphylococcus aureus. Functional analysis revealed that proteins involved in carbohydrate and ribonucleotide metabolism, stress response and virulence gene expression were affected by cspA deletion. Stress-associated phenotypes such as increased bacterial aggregation and diminished resistance to oxidative-stress stood out. Integration of the proteome and targetome showed that CspA post-transcriptionally modulates both positively and negatively the expression of its targets, denoting additional functions to the previously proposed translation enhancement. One of these repressed targets was its own mRNA, indicating the presence of a negative post-transcriptional feedback loop. CspA bound the 5′UTR of its own mRNA disrupting a hairpin, which was previously described as an RNase III target. Thus, deletion of the cspA 5′UTR abrogated mRNA processing and auto-regulation. We propose that CspA interacts through a U-rich motif, which is located at the RNase III cleavage site, portraying CspA as a putative RNase III-antagonist.